DISRUPTING THE EPIGENOME IN NOVEL NICE MICE TO STUDY AGE-RELATED COGNITIVE DECLINE. (11th November 2018) - Ross, J M; Coppotelli, G; Amorim, J; Hillstedt, E; Potts, E; Sinclair, D
Abstract: Aging of the brain is a cause of cognitive decline and the major risk factor for neurodegenerative diseases, such as Alzheimer's disease. Epigenetic noise has been highly implicated in both aging per se and cognitive impairment. In order to delineate the role of epigenetics in age-related cognitive decline, we are investigating two novel models that allow for precise control and tissue specificity in inducing non-mutagenic, site-specific double-strand DNA breaks by using the homing endonuclease I-PpoI. The ICE mouse has whole-body Inducible Changes in the Epigenome, whereas the NICE mouse has Neuronal-specific Inducible Changes in the Epigenome. Barnes maze results demonstrate that 15 month-old ICE mice under-performed with regards to memory recall, compared to age-matched Cre controls. Additionally, while ICE mice were able to learn the paradigm similarly well as controls, they employed unusual learning strategies. In the elevated plus maze, ICE mice spent more time in and actively sought out the open arms suggesting a decrease in thigmotaxis. Although no major impairments in spatial working memory were detected with the Y-maze, open-field testing showed an increase in time spent in the center of the arena. The NICE mouse has successfully been generated, with offspring viable and healthy. Western blot and immunohistochemistry analyses confirm induction of I-PpoI expression in key brain regions, including cerebral cortex and hippocampus, but not in peripheral tissues. Ongoing studies aim to elucidate how DNA damage and chromatin remodeling can elicit neuronal functional changes, which may identify treatment strategies for age-related diseases and disorders of the brain.